2009
DOI: 10.1002/bjs.6587
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival after hepatic artery embolization in patients with midgut carcinoid syndrome

Abstract: HAE is safe, provides good control of hormonal symptoms, and prolongs survival in biochemically responsive patients. It is a valuable palliative option for patients with midgut carcinoid syndrome due to liver metastases and can be repeated in patients with a favourable response to the first procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…Numerous studies have shown that HAE and HACE are effective in controlling hormonal symptoms and reducing tumor size [14,15,17,19,21,22,23,24,25,26]. The tumor response rates are variable in the literature (33–92%) [14,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that HAE and HACE are effective in controlling hormonal symptoms and reducing tumor size [14,15,17,19,21,22,23,24,25,26]. The tumor response rates are variable in the literature (33–92%) [14,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The median OS was not evaluable and the analysis of predictive factors of OS was not relevant due to the small number of deaths. In the literature, the 2-year OS rates after treatment of midgut endocrine liver metastases were 67–80%, with a median OS near 40 months (range 31–80) [19,24,26]. The percentages of changes in urinary 5-HIAA and serum chromogranin A levels were correlated with prolonged survival in one study and have been proposed to be used as predictors of long-term outcome [26].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the favorable tumor biology of well-differentiated (G1) NETs of the ileum, an elective, palliative operation performed in a specialized center should be discussed as part of a multimodal approach. Please refer to recent review papers for multimodal therapy of neuroendocrine liver metastases [18,[67][68][69][70][71][72] .…”
Section: Management Of Ileal Netsmentioning
confidence: 99%
“…Symptomatic response is achieved in 40-80%, biochemical response in 50-60% with overall 5-year survival, and 50-60% post-embolisation , Brown et al 1999, Dominguez et al 1999, 2000, Kim et al 1999, Yao et al 2001, Roche et al 2003, Marrache et al 2007, Sward et al 2009). The mechanism is to induce ischaemia in tumour cells, thus reducing their hormone output.…”
Section: Embolisation and Ablative Methodsmentioning
confidence: 99%